Healthcare Security In Tactical Emergency Medical Services: Medical Care And Casualty Evacuation Under Active Threat Conditions (The Review of Diabetic Studies, 2024)
Background: High‑threat law enforcement operations have accelerated the integration of Tactical Emergency Medical Support (TEMS) into police missions, translating battlefield lessons to the civilian domain. TEMS emphasizes threat‑calibrated care, structured operational zoning (hot/warm/cool), rapid and remote assessment, and a trauma sequence that prioritizes exsanguination control (XABCDE). It also formalizes extraction and evacuation pathways and demands disciplined interagency communication and healthcare security practices.Aim: To synthesize a healthcare security–focused framework for medical care and casualty evacuation under active threat, delineating competencies, decision processes, and operational enablers that optimize survivability while safeguarding responders.Methods: Narrative synthesis of doctrinal principles and practice guidance described in the article, mapping core elements—zonal care, rapid and remote assessment methodology (RRAM), XABCDE, extraction modalities, evacuation coordination (ground and air), and communication protocols—into a coherent, operational model. Simulation insights on extraction devices and commonly deployed en‑route critical care capabilities are incorporated.Results: A threat‑informed continuum is defined: in the hot zone, self‑care and rapid movement to cover predominate; in the warm zone, providers balance immediate life‑saving intervention against residual risk; in the cool zone, bundled care and organized transport proceed. RRAM provides a stepwise risk–benefit algorithm, while XABCDE operationalizes clinical priorities (tourniquets, chest seals, decompression, permissive hypotension, selective airway strategies). Extraction emphasizes longitudinal drags, vest‑assisted control, and the judicious use of rigid/soft stretchers and armored shielding; evacuation stresses preplanned EMS interfaces, capacity for blood products, vasopressors, and ventilation, and contingencies for law‑enforcement or rotary‑wing transport. Communication discipline underpins security, tempo, and clinical accuracy.Conclusion: Implementing this integrated model can reduce preventable mortality and provider harm by aligning medical interventions with tactical realities, standardizing communication, and rehearsing extraction–evacuation workflows.